Maternal environmental enrichment affects the corpora lutea and progesterone levels in pregnant mice - De la Cruz Borthiry, Fernanda Luz; Beltrame, Jimena Soledad; Schander, Julieta Aylen; Silva, Aime Florencia; Parborell, Fernanda; Franchi, Ana María; Ribeiro, María Laura (Frontiers in Endocrinology, 2025)
IntroductionMaternal lifestyle impacts reproductive performance. Previously, we demonstrated that maternal environmental enrichment promotes pregnancy success in BALB/c mice. As progesterone regulates gestation, we decided to study the effect of maternal environmental enrichment on ovarian physiology during early gestation.MethodsFor this, six-week-old female mice were housed in enriched or control cages for six weeks and then mated with control fertile males. Females with a mucus plug were returned to their respective control or enriched cages. Pregnant mice were euthanized on day 7 of pregnancy, and ovaries and progesterone levels were investigated.ResultsHematoxylin and eosin slices showed no differences in the area (μm2) of the ovaries between control and enriched females. Also, the number of primordial, primary, preantral, antral, and atretic follicles was similar for both treatments. However, the number and area (μm2) of corpora lutea were increased in the ovaries from the enriched group. Moreover, enriched females presented higher progesterone serum levels and increased 3β-HSD expression.DiscussionTherefore, maternal environmental enrichment regulates ovarian physiology, and this could promote the benefits previously reported.